Bioconcentration and translocation of rare earth elements in plants collected from three legacy mine sites in Portugal - Forsyth, Kaisa; Dia, Aline; Marques, Rosa; Prudêncio, Maria Isabel; Diamantino, Catarina; Carvalho, Edgar; Russo, Dulce; Dionisio, Isabel; Davranche, Melanie; Bouhnik-Le-Coz, Martine; Pédrot, Mathieu (Frontiers in Environmental Science, 2023)
Rare earth elements (REE), a group of emerging contaminants with commercial and technological applications, share many physical and chemical characteristics and have thus been used as accurate tracers of various environmental samples. They have been shown to increase in receiving waters following the dissolution of host-rock material during mining activities. In this study, spontaneous vegetation and related media were collected from three Portuguese legacy mine sites in November 2020 to evaluate the phytoavailability and fate of REE. Water, soil and plant data were analyzed in the context of the 1) prevailing geochemical context, 2) the mining context, and 3) plant effects. This study presents the REE signatures for different plant species and links the signatures to a potential source of bioavailable REE. The REE accumulated in plant tissue seems to reflect the REE signature of surface waters in the mining areas, showing enrichment in middle REE. Although the soils, sediments, and waters in this study had similar features, certain plants seemed better adapted to translocating Light REE and Eu over others. Given that REE are readily available within the field conditions of a mining site, this study shows how plant physiology and biologic preference towards particular REE contribute to the fractionation of REE and create a unique signature dependent on plant type.